PENGARUH FASILITAS TERHADAP KEPUASAN TAMU MENGINAP DI HANNAH HOTEL SYARIAH PAINAN - Wedi Andesta (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2019)
This study aims to determine the effect of room facilities on guest satisfaction staying at Hannah Hotel Syariah Painan. This research is a quantitative descriptive study with a causal associative approach. The number of samples in this study were 82 samples. The sampling method is propotionate stratified random sampling. Data is collected by questionnaire using a Likert scale. The data analysis technique used in this study is descriptive analysis using simple linear regression analysis. The results of this study indicate that: (1) room facilities are in the good category 54.88%, (2) guest satisfaction is in the excellent category 40.24%, (3) there is a guest satisfaction value increased by 16.843 units, there is a positive influence and significant between room facilities to guest satisfaction staying at Hannah Hotel Syariah Painan. The R square value obtained is 0.174, this means that room facilities variables have an effect of 17.4%.